The long-term trend of uterine fibroid burden in China from 1990 to 2019: A Joinpoint and Age–Period–Cohort study - Liu, Xingyu; Wang, Bo; Zhang, Qianyu; Zhang, Jinjin; Wang, Shixuan (Frontiers in Physiology, 2023)
Purpose: Uterine fibroids occur in 40%–60% of women and are symptomatic in 30% of the patients by causing abnormal uterine bleeding, pelvic pressure, pain, and infertility. The study aims to evaluate the long-term trend of uterine fibroids mortality and disability-adjusted life years (DALYs) in China and the relative risks of age, period, and birth cohort effects. Methods: The mortality and DALYs of uterine fibroids from 1990 to 2019 were derived from the Global Burden of Disease 2019. The annual percentage change and average annual percent change (AAPC) were assessed using the Joinpoint regression. The effects of age, period, and birth cohort on death and DALYs were analyzed by the Age–Period–Cohort framework. Results: The age-standardized rates were all on the ascending trend, with the greatest increase in the age-standardized mortality rate (AAPC, 1.53; 95% CI, 1.04–2.02). The net drift was found to be 3.51% (95% CI, 2.25%–4.78%) per year for mortality and 0.34% (95% CI, 0.14%–0.53%) per year for DALYs. Significant age, period, and birth cohort effects were found for mortality and DALYs (p < 0.001 for all). The mortality risk increased overall with age, but the DALYs risk increased first and then decreased with age. The period and birth cohort risks for mortality and DALYs showed different trends. Conclusion: These secular time trends and changes of mortality and DALYs reveal the socioeconomic alterations, reform of diagnosis and therapy, and changes in social lifestyles and behaviors. Uterine fibroids are still the most common benign gynecological tumors in women, and more epidemiological investigations and social health prevention and control should be applied.